Short term outcomes of snodgrass urethroplasty in distal and mid penile hypospadias - S., Pramod; J., Anukethan (International Surgery Journal, 2018)
Background: Hypospadias is common congenital condition. First attempted hypospadias surgery was done during first century A.D. Since then more than 300 techniques have been explained in the surgery for Hypospadias. The goal of surgery is focused on functional and cosmetic outcomes. In 1994 Snodgrass popularized the technique of urethral plate incision, tubularization and secondary dorsal healing for hypospadias repair. Aim of the study was to evaluate the short term outcomes of Snodgrass urethroplasty. Methods: This was a retrospective study conducted by the department of Pediatric Surgery, Kempegowda Institute of medical sciences (KIMS) hospital, Bangalore from 2014 to 2017. Children with mid penile and distal hypospadias who had undergone Snodgrass urethroplasty were enrolled in the study. Children with previous surgery were excluded. The demographic data, duration of surgery, post operative requirement of anticholinergics, duration of catheterization and post operative stay were tabulated. Children were followed up for duration of 6 months to 3 years. Post operative complications were tabulated. Results: 40 children were included in the study. Age ranges of children were between 9 months to 14 years. In most of the children hypospadias was diagnosed at birth. The mean duration of surgery was 97.25 minutes. The mean duration of hospitalization was12.2 day. The overall complications rate was 20%. The most common complication was urethrocutaneous fistula. Out of the 40 children included in the study 4(10%) children required resurgery (urethrocutaneous fistula closure). Conclusions: Snodgrass urethroplasty is a simple and effective technique. It is easy to learn and can be applied as a single stage procedure. The most common complications are urethrocutaneous fistula and meatal stenosis.